HUBUNGAN LINGKAR PERUT, KONSUMSI GULA DAN LEMAK DENGAN KADAR GLUKOSA DARAH PEGAWAI DIREKTORAT POLTEKKES KEMENKES JAKARTA II - Adwinda, Marina Dwina; Srimiati, Mia (Jurnal Nutrire Diaita (Ilmu Gizi), 2019)
Consuming excessive amounts of sugar and fat can cause increased abdominal circumference. This condition can lead to central obesity that closely related to hyperglycemia which is the early signs and symptoms of non-communicable diseases (NCD). The aim of this study was to analyze the correlation between abdominal circumference, consumption of sugar and fat with blood glucose levels in employees of Directorate Poltekkes Kemenkes Jakarta II. This research was conducted at Directorate Office of Poltekkes Kemenkes Jakarta II. The study design was cross sectional in 39 healthy adults, using simple random sampling. The data of sugar and fat consumption were obtained from 2x24 hours food recall interview. The abdominal circumference was measured using metlin, and fasting blood glucose was measured using glucometer. The analytical tests used Spearman. There were a correlation between sugar consumption (p = 0.000, r = 0.613) and abdominal circumference (p = 0.028; r = 0.352) with fasting blood glucose but there was no correlation between fat to fasting blood glucose. In addition consumption of sugar and abdominal circumference were correlated to fasting blood glucose.Keywords: abdominal circumference, consumption of sugar and fat, fasting blood glucose levels